ANALYSIS OF GENETIC DIVERSITY OF OSPHRONEMIDAE FAMILY FISHES USING THE RAPD-PCR METHOD - Yuniar Mulyani; Aisyah Aisyah; Eulis Reni Sundari (Universitas Mataram, 2024)
Currently research on genetic diversity analysis is needed and is important information to maintain its survival. Osphronemidae family fish are fish that are often found in various regions. Generally, fish from this family are ornamental fish which are characterized by having a variety of colors. This requires supporting data to determine the level of relationship between fish in the Osphronemidae family. Therefore, research was carried out on the genetic diversity of fish in the Osphronemidae family using the RAPD-PCR method. The research was carried out using goldfish (MK), Blue gourami (SP), gourami (GM), dumbo ear betta (DE), crowntail betta (ST), wild betta (WB), and halfmoon betta (HM). The stages carried out are sample preparation, isolation, PCR, data analysis. The results showed that the fourth highest level of kinship was between SP3 (Blue gourami), GM1 (gourami), WB19 (wild betta), DE3 (dumbo ear betta), ST10 (crowntail betta), and HM3 (halfmoon betta), namely 0.18 or 18%. Meanwhile, the sample included in the outgroup is MK1 (goldfish) has no relationship with other samples.